Advances in Reliability and System Engineering - Ram, Mangey; Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents original studies describing the latest research and developments in the area of reliability and systems engineering. It helps the reader identifying gaps in the current knowledge and presents fruitful areas for further research in the field. Among others, this book covers reliability measures, reliability assessment of multi-state systems, optimization of multi-state systems, continuous multi-state systems, new computational techniques applied to multi-state systems and probabilistic and non-probabilistic safety assessment.
Reliability measures, reliability assessment of multi-state systems -- System Engineering -- Reliability Modeling and Testing for Complex Systems -- Optimization of multi-state systems Continuous multi-state systems -- Standby multi-state systems -- New computational techniques applied to multi-state systems -- Mathematical Modelling & Simulation -- System reliability improvement and preventive maintenance based on component degradation -- Probabilistic and non-probabilistic safety assessment -- monitoring and control for multi-stage systems -- Engineering design for safety and reliability -- Statistical process control -- System modelling.
Keywords: Security systems; Electronic circuits; Engineering mathematics; Engineering -- Data processing; Security Science and Technology; Electronic Circuits and Systems; Mathematical and Computational Engineering Applications